Design and Techno-Economic Evaluation of a Solar Photovoltaic Groundwater Pumping System for Irrigation and Rural Water Supply in Punjab, India - Muhammad Zurhalki; Najib Hassan; Andika Prasetiadi; Xinhui Wang; Joydip Saha; Nanang Dwi Wahyono (Balai Publikasi Indonesia, 2026)
Diesel-powered groundwater pumping remains common in Indian agriculture, contributing to high fuel use, costs, and greenhouse gas emissions. With rising irrigation demand and groundwater stress, an accelerated transition to low-emission irrigation technologies is increasingly urgent. This study assesses the technical and economic feasibility of replacing diesel-powered pumping with a solar photovoltaic (PV) system in Punjab, India. A 10 kWp PV system was found to reliably meet irrigation demand for one hectare of paddy cultivation and typical domestic water needs under seasonal variability. Life Cycle Cost and Break-Even analyses over a 15-year horizon show substantially lower costs than diesel pumping, with a break-even point in the first year under a replacement scenario. The PV system also reduces operational emissions by approximately 4.6 t CO₂e per rice growing season, supporting sustainable irrigation transitions in groundwater-dependent regions